2021
DOI: 10.1111/liv.14669
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic accuracy of FIB‐4, NAFLD fibrosis score and APRI for NAFLD‐related events: A systematic review

Abstract: Background & Aims Fibrosis is the strongest predictor for long‐term clinical outcomes among patients with non‐alcoholic fatty liver disease (NAFLD). There is growing interest in employing non‐invasive methods for risk stratification based on prognosis. FIB‐4, NFS and APRI are models commonly used for detecting fibrosis among NAFLD patients. We aimed to synthesize existing literature on the ability of these models in prognosticating NAFLD‐related events. Methods A sensitive search was conducted in two medical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
148
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(194 citation statements)
references
References 46 publications
10
148
2
7
Order By: Relevance
“…D-Assessment of disease determinants in individual patients is not routinely performed in clinical practice nor in RCTs despite the fact that a variety of pathogenic risk factors are well characterized. In our view, all the following features are important modifiers that are worth registering in the individual patient and should be taken into consideration in therapeutic [193,194] AST, platelets studies: (i) sex and reproductive status, (ii) genetics, (iii) intestinal microbiota, (iv) endocrine assessment, (v) metabolic assessment, and (vi) physical activity. Existing data on the role of these factors in NAFLD are summarized in ''Sex, Gender, and Reproductive Status''.…”
Section: Diagnosismentioning
confidence: 99%
“…D-Assessment of disease determinants in individual patients is not routinely performed in clinical practice nor in RCTs despite the fact that a variety of pathogenic risk factors are well characterized. In our view, all the following features are important modifiers that are worth registering in the individual patient and should be taken into consideration in therapeutic [193,194] AST, platelets studies: (i) sex and reproductive status, (ii) genetics, (iii) intestinal microbiota, (iv) endocrine assessment, (v) metabolic assessment, and (vi) physical activity. Existing data on the role of these factors in NAFLD are summarized in ''Sex, Gender, and Reproductive Status''.…”
Section: Diagnosismentioning
confidence: 99%
“…It has been reported that advanced fibrosis is a crucial prognostic factor for NAFLD. Several studies have revealed that APRI and FIB-4 can stratify the risks of liverrelated morbidity and mortality [29]. This study found that liver fibrosis scores showed statistically significant differences between the TAM and TOR groups, independent of obesity and diabetes.…”
Section: Discussionmentioning
confidence: 49%
“…Prediction rules based on a combination of serological biomarkers, such as FIB-4, are slowly paving the way to more acceptable and affordable indicators for the identification of patients at high-risk of progressive disease, which could be successfully used in primary care for diagnosis and adequate referral to specialised services. 52,53 Unfortunately, patients with NAFLD, including those with NASH associated advanced fibrosis or cirrhosis, often remain undetected until an incidental diagnosis or decompensation of liver cirrhosis, which contributes to increasing trends in NAFLD-related morbidity and mortality. This ineffective "filter" at the primary care level due in part to inadequate knowledge of non-invasive surrogate J o u r n a l P r e -p r o o f markers of fibrosis 54 could be improved by the use of defined care pathways which utilise a NAFLDspecific stepwise algorithm to guide clinical decisions and to improve referral to specialised services.…”
Section: Discussionmentioning
confidence: 99%